History of use and abuse of X-ray: the early 20th century Italian pediatrics school - Vardeu, Maria Francesca; Larentis, Omar; Vecchio, Ignazio; Gorini, Ilaria; Martini, Mariano; Bragazzi, Nicola; D'Ambra, Antonello; Ruggieri, Martino; Tornali, Cristina (Acta Biomedica Atenei Parmensis, 2020)
In our paper we report a brief history of the X-rays discovery and discuss the implications of their use and abuse in the Italian pedriatic schools of the early 20th century. Indeed, history of the X-ray treatment in the Italian Pediatric School has not yet been well studied. Even if the scientific experience of many physicians is well known in literature, a summary was missing. In Italy, in 1900, exposure to Röntgenand ultraviolet radiation or to large amounts of solar rays was a widespread medical practice, especially in several pediatric schools. During those years, diagnosis and treatment of childhood pathologies underwent considerable changes, especially after the twenties, when scientists developed an unquestionable trust in the therapeutic properties of radiation, considered harmless at that time. We report the main steps of the scientific research of the early 20th century in Italy.